Explosive Risk Assessment for Hydrogen Use in Domestic Applications - Thawani, Bonny (Cranfield University, 2022)
The UK government aims to shift towards hydrogen-based energy for domestic applications between 2028-2035. While hydrogen is a carbon neutral resource, it has a very low ignition energy (0.019mJ) and high flammability range (4-75% in air). This project aims to understand the use of hydrogen in the natural gas network as a replacement for methane and especially assess the explosive threat posed by this. More specifically, the project focuses on the simulation (and experimental validation) of hydrogen gas flow in pipes and enclosed spaces (such as boiler cabinets) to enable visualisation of the explosive threat (including deflagration-to-detonation transition) in case of an accident. Mathematical and computational simulations were used to estimate the pressure loss of gases in pipes of different diameters (0.01m - 1m) and materials (Polyethylene and X52 steel). Simulations for the turbulent flow of hydrogen and methane in pipes of different diameters showed that hydrogen has to be transported at approximately 2.5-2.7 times the velocity used for methane, to replicate the pressure loss per meter. From the mathematical models, it was noted that different pipe materials influence the pressure loss in turbulent gas flow due to the relationship between absolute roughness of the material and friction factor. While the mathematical model and computational model have slightly different approaches to estimate turbulent flow, the results from the two are largely in agreement with an approximate error of 10%.
Keywords: Hydrogen; Modelling and Simulation; Security; DSDS22; DSDS22 Poster